Agriculture, Natural Resources and Food Security Lessons from Nepal - Timsina, Jagadish; Maraseni, Tek N.; Gauchan, Devendra; Adhikari, Jagannath; Ojha, Hemant (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explains how a former net food exporting Nepal has become a net food importing country due to a lack of an integrated system-wide approach to planning and governance of agriculture and natural resources. It demonstrates how various components of the food system, such as agronomy, agrobiodiversity, plant health, post-harvest management, livestock and fisheries, and socio-economics including marketing and trade, have been managed in sectoral silos, crippling the very foundations of food systems innovations. The book also explores ways to tackle climate change impacts while considering gender, social equity, conservation agriculture practices, and crop modeling as cross-cutting themes. This book utilizes Nepal as a case study in relation to wider questions of food security and livelihoods facing South Asia and synthesizes lessons that are relevant to the Global South where countries are struggling to harmonize and integrate natural resources management for sustainable and effective food security outcomes. As such, it significantly contributes to the knowledge toward achieving various United Nations Sustainable Development Goals.
Urban agriculture for maximizing social and economic benefit to the people -- Development and application of crop and system models: Opportunity to increase food, nutrition, and livelihood security in Nepal -- Agrobiodiversity and neglected and underutilized species for food and nutrition security in Nepal -- Contribution of soil and soil research to food security in Nepal -- Plant health clinics for improved crop management and food security: Nepalese experience and way forward. .
Keywords: Human geography; Food security; Climatology; Agriculture; Agriculture-Economic aspects; Human Geography; Food Security; Climate Sciences; Agriculture; Agricultural Economics